ANALISIS PENERAPAN SAK-EMKM PADA PELAKU USAHA KECIL, DAN PELAKU USAHA MENENGAH - Kuntum Lathifatur Rosyidah; Shelawati Ariningsih; Rita Wijayanti (Faculty of Economics and Business, 2022)
The purpose of this study is to determine the model for preparing the shop financial statements and to determine the knowledge and understanding of shop owners about SAK EMKM. This study uses a descriptive qualitative approach. To find out the application of SAK EMKM at the shop, the researcher used direct observation and interview techniques. The results of this study indicate that the Sularmi shop did not make financial reports at all and did not understand the application of SAK EMKM. This study only focuses on one sample of small businesses. The limitations of the research experienced were that the shop owners did not know about SAK EMKM at all. The possibility of contributing to the implementation of SAK EMKM has not been able to contribute because of the low understanding of SAK EMKM. However, we hope to provide assistance to improve understanding, knowledge, and skills of accounting practice as well as to analyze working capital needs in Sukoharjo Regency.